Menghadirkan Keceriaan, Kebahagiaan, Resiliensinya sebagai Pendekatan Strategis dan Religius dalam Proses Pembelajaran - Mustofa, Ahmad Ali (TSAQOFAH, 2025)
Cheerfulness, happiness, and resilience are fundamental elements in an effective and meaningful learning process. Happiness not only creates an enjoyable learning atmosphere but also strengthens students' resilience in facing challenges. From an Islamic perspective, happiness has a profound spiritual dimension, providing a strong foundation for students to remain steadfast and optimistic in their learning journey. Creative approaches, such as interactive methods, engaging media, project-based learning, and gamification, can foster a learning environment that supports students' emotional and intellectual growth. By integrating religious values and creative strategies, the learning process not only achieves strong academic outcomes but also shapes students with resilient character, the ability to endure adversity, and a balanced perspective between worldly and spiritual pursuits. This holistic approach significantly contributes to nurturing a generation of learners who can face life's challenges with optimism, resilience, and joy.